The Relationship Of Body Mass Index (BMI) With Vo2max In Students At Stikes Rs Dustira - Nabillah, Lily; Ahmad Dwi Marwiyanto; Fatia Maulida Meiliana (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Students generally do not exercise, in fact they tend to choose habits with very poor sleep and rest patterns and consume food labeled fast food. The student's lifestyle has an indirect impact on fitness levels and nutritional status as measured by body mass index. One variable that influences cardiovascular fitness levels is body mass index (BMI). An increase in fat tissue in the body will occur if a person's BMI value is high and is classified as overweight or even obese. In this research, the quantitative research method uses correlational analysis. The population in the study was Dustira Hospital STIKes female students, totaling 51 people. Data were collected by measuring height, weight, and carrying out the Cooper test to measure VO2max levels. The results of the research show that the significance value of the Spearman Rho Correlation with the value (p) of the two variables is 0.001, which means that the two variables have a significant relationship, namely between Body Mass Index (BMI) and VO2Max level (p<0.05). Based on the correlation test, the correlation coefficient (r) was obtained at -0.550, which means that the two variables have a strong relationship between Body Mass Index (BMI) and VO2Max, which is strongly correlated and the correlation between the variables is negative. This is stated that the higher the BMI, the lower the VO2max cardiorespiratory endurance level, while the lower the BMI, the higher the VO2max cardiorespiratory endurance level.